2012
DOI: 10.1590/s1519-69842012000100026
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of interaction between Meteorus sp. Haliday, 1835 (Hymenoptera: Braconidae) and its hyperparasitoid Toxeumella albipes Girault, 1913 (Hymenoptera: Pteromalidae)

Abstract: Some parasitoids build a cocoon mass that hangs in the host body until the adults emergence, which is an advantage against attack by predators who troll the vegetation in search of prey. However, such behaviour is not effective against the hyperparasitoid attacks. This study reports the interaction between the caterpillar Manduca sexta Linnaeus, 1763 (Lepidoptera, Sphingidae) parasitised by Meteorus sp. (Hymenoptera, Braconidae) larvae and its hyperparasitoid Toxeumella albipes (Hymenoptera, Pteromalidae). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Also the Meteorus sp. 1 (Hymenoptera: Braconidae), which was found in great abundance, is a parasitoid of the Lepidoptera larvae (Berry et al, 2016;Sobczak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Also the Meteorus sp. 1 (Hymenoptera: Braconidae), which was found in great abundance, is a parasitoid of the Lepidoptera larvae (Berry et al, 2016;Sobczak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Harvey et al 2011found that Gelis agilis (Fabricius) parasitized M. pulchricornis in suspended cocoons to about the same extent as it did in cocoons attached to leaves. Moreover, Sobczak et al (2012) observed that a female wasp of the pteromalid hyperparasitoid Toxeumella albipes Girault flew directly into a cocoon mass made by a gregarious Meteorus species.…”
Section: Does Cocoon Suspension Offer Protection Against Hyperparasitmentioning
confidence: 99%